Participants in criminal proceedings: problematic issues of classification - A. F. Volobuyev (Bulletin of Kharkiv National University of Internal Affairs)
The article analyzes the conceptual approach that was used by the legislator to classify participants in criminal proceedings. It is noted that the current classification into participants in criminal proceedings and participants in judicial proceedings looks very illogical, since the concept of criminal proceedings also includes judicial proceedings as a separate stage. In addition, the specified classification groups do not include a court and an investigating judge, but the secretary of the court session and the court administrator are present. The purpose of the article is to formulate proposals for improving the classification of participants in criminal proceedings on the basis of clarifying the functions they perform and taking into account the rights granted to them and the duties assigned to them. To achieve the set goal, the following main scientific tasks were solved: to analyze the norms of the Code of Criminal Procedure of Ukraine regarding the determination of the status and classification of participants in criminal proceedings; to analyze scientific publications after the adoption of the Code of Criminal Procedure of Ukraine in 2012, devoted to participants in criminal proceedings; using a systemic approach to determine the connections between participants in criminal proceedings with their distribution by stages of criminal proceedings and functions performed.